ความพึงพอใจของคนกลางที่มีต่อส่วนประสมการตลาดของแหนมป้าย่น - ชวนะ นิรัติศยวานิช (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The study on “Satisfaction of Middlemen Towards Marketing Mix of Nham Pa Yon” collected data from 103 middlemen. The findings presented that most respondents were female in the age of 41-50 years old, whose education background was lower than bachelor’s degree. They were business owners with over 6 years of experience in ordering Nham Pa Yon products. Their business had been operated for more than 15 years and was registered as the single owner. In a month, the sale volume of Nham Pa Yon products was found between 10,000-50,000 Baht and the frequency of ordering the products was more than 6 times. They made orders to the studied products via telephone when the inventory was finished. Their customers were general consumers. According to the study, the marketing mix factor that the respondents paid the highest level of satisfaction was place; followed by product, price and promotion factors, respectively. In an overview, the respondents were satisfied with the marketing mix factors at satisfy level. For product factor, the top three elements satisfying them the most were product fame and product reliability, consistency of product quality as being certified by the Good Manufacturing Practice (GMP) and the Food and Drug Administration, including hygiene of product without any diluted substance, and product development such as bio-sour pork (Nham) / Biotech, respectively. For price factor, the top three elements satisfying them the most were clear price detail, reasonable price comparing to product quality, and availability of credit term payment. For place factor, the top three elements satisfying them the most were accurate delivery process which product type and quantity were delivered correctly according to orders, standard of product delivery without damage, and punctuality of product delivery. For promotion factor, the top three elements satisfying them the most were polite and friendly salesperson with good manner while serving customers, salesperson who was knowledgeable on products and could provide correct information, and supports to activities such as sport events, children’s day, and social supports. Problems that those middlemen found were listed hereafter. In product factor, the problem was lack of variation of product size packages. In price factor, the problems were non-negotiable price, unreasonable price comparing to product quantity, higher price of products offered in compare to other distributors, irregular notice on product prices, and unreasonable price comparing to product quality, respectively. In place factor, the problem was the limitation of manufacturer in delivering products for urgent demand. In promotion factor, the problems were to have no discount, to have no cash discount, to offer none of giveaway for shops, and lack of image building for shops or distributors via point-of-purchase advertising, for example.